Computational simulation of aortic aneurysm using FSI method: Influence of blood viscosity on aneurismal dynamic behaviors - Wang, Xiaohong; Li, Xiaoyang (Computers in biology and medicine, 2011)
It is well-established that blood viscosity plays a significant role in the determination of the health of the individual. It has been reported that many cardiovascular diseases are associated with blood viscosity. In this paper, the dynamic behaviors of aortic aneurysm subject to physiological blood flow with normal and high viscosities are presented. Fluid–structure interaction (FSI) method was used in the computational simulation. The influence of blood viscosity on flow dynamics within the aneurysm sac, aneurismal diameter, cross sectional shape, wall axial displacement and wall shear stress (WSS) was studied in detail. This investigation uncovered the correlations between blood viscosity and the dynamic behaviors of aortic aneurysm, which have rarely been found in existing literatures. We believe that these findings may provide important implications for individualized endovascular treatment for patient with aortic aneurysm.